Penerapan Model PBL untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas VIII-5 SMPN 45 Pekanbaru - Karisma, Romi; Siregar, Syarifah Nur; Saragih, Sehatta (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study was motivated by the low mathematics learning outcomes of class VIII-5 students at SMPN 45 Pekanbaru on the topic of the Pythagorean Theorem, where only 14 out of 36 students (38.9%) met the Minimum Criteria for Learning Objective Achievement (KKTP). Observations revealed that the learning process had not fully implemented the stages of the Problem Based Learning (PBL) model, which emphasizes student-centered learning through problem identification, group collaboration, exploration, and evaluation. The aim of this study was to improve the learning process and enhance student achievement in mathematics by applying the PBL model. This research employed a collaborative Classroom Action Research (CAR) approach, conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection phases. The research subjects were 36 students of class VIII-5 at SMPN 45 Pekanbaru in the 2024/2025 academic year. Data were collected using observation sheets for teacher and student activities, as well as mathematics achievement tests. The results showed that the implementation of the PBL model had a positive impact on student and teacher activity during the learning process. The percentage of students who achieved the KKTP increased from 38.9% in the pre-cycle to 50% in cycle I and 66.7% in cycle II. These findings indicate that the application of the PBL model successfully improved the learning process and student mathematics achievement. Therefore, this model is recommended as an effective instructional approach to enhance the quality of mathematics education in junior high schools.